1976
DOI: 10.1128/aac.9.5.754
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of Antibiotics Using High-Pressure Liquid Chromatography: Tetracycline

Abstract: A method for quantitative determination of tetracycline in serum, using highpressure liquid chromatography, is reported. After extraction of the drug from serum, using methanol-trichloroacetic acid solution, tetracycline was separated by reverse-phase chromatography. Quantitation of tetracycline was based on a linear relationship between peak heights in the chromatograms and known concentrations of the drug in the original serum samples. Serum

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

1977
1977
1985
1985

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…If the microbial assay values were compared with those of cephalothin alone, desacetylcephalothin alone, or the sum of cephalothin plus desacetylcephalothin (all determined by the chemical assay), the correlation coefficients were 0.79, 0.84, and 0.80, respectively. This lower correlation coefficient in dogs may be due to the higher concentrations of desacetylcephalothin in the sera of Recently, the HPLC technique has been successfully implemented for rapid, accurate, and specific measurements of tetracycline (13) and amphotericin B (12) in serum and cerebrospinal fluid. The complete methodology involved simple extraction of antibiotics from the samples, followed by separation by HPLC and, finally, detection of the compounds by ultraviolet spectrometry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the microbial assay values were compared with those of cephalothin alone, desacetylcephalothin alone, or the sum of cephalothin plus desacetylcephalothin (all determined by the chemical assay), the correlation coefficients were 0.79, 0.84, and 0.80, respectively. This lower correlation coefficient in dogs may be due to the higher concentrations of desacetylcephalothin in the sera of Recently, the HPLC technique has been successfully implemented for rapid, accurate, and specific measurements of tetracycline (13) and amphotericin B (12) in serum and cerebrospinal fluid. The complete methodology involved simple extraction of antibiotics from the samples, followed by separation by HPLC and, finally, detection of the compounds by ultraviolet spectrometry.…”
Section: Resultsmentioning
confidence: 99%
“…Recently we have successfully applied highpressure liquid chromatography (HPLC) to the quantitation of antibiotics in serum and cerebrospinal fluid (12,13). This technique has advantages over standard microbiological assays with regard to accuracy, specificity, and rapidity.…”
mentioning
confidence: 99%
“…An HPLC technique for the analysis of tetracycline after extraction from serum has recently been reported by Nilsson-Ehle et al (4). Cooper et al (2) reported on the use of HPLC, employing anion exchange chromatography of cephalothin and deacetylcephalothin after ion pair extraction from human serum.…”
mentioning
confidence: 99%
“…Several authors have reported on the use of reverse phase methods for the determination of tetracyclines. 7,8,9,10) For reasons discussed in our previous paper1), we prefer to use reverse phase instead of ion exchange chromatography for antibiotics. However, ion exchange high pressure liquid chromatography has also been used successfully for the analysis of cephalosporins,11, 12,13) penicillins 14, 151 and tetracyclines.…”
mentioning
confidence: 99%